Politik Hukum Hak Asasi Manusia di Indonesia - Moh. Mahfud MD (Fakultas Hukum Universitas Islam Indonesia, 2000)
Although Indonesia has adopted the principles of legal state (the rule of law) and democracy the abuse of human rights, particularly the massive and intensive abuse forms, still occurs. This article tries to overview the problem in the legal politic aspects, considering the available legal instalment and formulation in the constitution and the legal devices of its enforcement. For short term of legal politics, there is a faced dilemma; doing the brave andstrict settlement until court, or conducting whitening by fair reconciliation. The choice between the two sides should be quickly carried out by previously calculating its procedural-technical obstructions and its political ones.